The Formosalides: Structure Determination by Total Synthesis. Issue 1 (3rd November 2020) - Schulthoff, Saskia; Hamilton, James Y.; Heinrich, Marc; Kwon, Yonghoon; Wirtz, Conny; Fürstner, Alois
Abstract: Total synthesis allowed the constitution of the cytotoxic marine macrolides of the formosalide family to be confirmed and their previously unknown stereostructure to be assigned with confidence. The underlying blueprint was inherently modular to ensure that each conceivable isomer could be reached. This flexibility derived from the use of strictly catalyst controlled transformations to set the stereocenters, except for the anomeric position, which is under thermodynamic control; as an extra safety measure, all stereogenic centers were set prior to ring closure to preclude any interference of the conformation adopted by the macrolactone rings of the different diastereomers. Late‐stage macrocyclization by ring‐closing alkyne metathesis was followed by a platinum‐catalyzed transannular 6‐exo‐dig hydroalkoxylation/ketalization to craft the polycyclic frame. The side chain featuring a very labile unsaturation pattern was finally attached to the core by Stille coupling. Abstract : Total synthesis allowed the identification of the most likely stereostructure of the cytotoxic marine macrolides of the formosalide family (see structure) from eight possibilities. The successful route was based upon an inherently flexible blueprint that builds all stereogenic centers by strictly catalyst controlled transformations prior to formation of the polycyclic framework by late‐stage alkyne metathesis followed by a π‐acid‐catalyzed transannular cyclization